A method for recycling of slurry for wet desulphurization of anode baking flue gas for aluminum

CN123002889APending Publication Date: 2026-10-30YUNNAN YUANXIN CARBON CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611059316.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-16
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

这些细小、不规则的晶体堆积密度低,孔隙多,水分难以排出,导致石膏结构不稳定

Benefits of technology

1、本发明通过在脱硫浆液中加入铝盐,加快了浆液的沉降速率,因此可以通过浆液分层情况快速判断杂质含量,从而确定回收工艺的参数,极大的缩短了脱硫浆液回收处理的时间,节约了处置成本,提高了经济效益。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123002889A_ABST
    Figure CN123002889A_ABST
Patent Text Reader

Abstract

The present application relates to the field of anode baking flue gas desulfurization slurry recovery technology for aluminum, in particular to a kind of recovery and utilization method of anode baking flue gas wet desulfurization slurry for aluminum.The method comprises the following steps: S1: sampling desulfurization slurry, adjusting pH value to 5.0~7.0, adding aluminum salt, determining the volume ratio of each layer in slurry;S2: the desulfurization slurry is adjusted to pH value 5.0~7.0, and aluminum salt is added, and cyclone dewatering is carried out, according to the volume ratio of each layer determined in step S1, the discharge amount of overflow is determined, and overflow and underflow are obtained;S3: the underflow is dewatered to obtain gypsum finished product;S4: the overflow is collected and purified, and then returned to desulfurization tower.The present application adds aluminum salt in desulfurization slurry, which speeds up the settling rate of slurry, so that the impurity content can be quickly judged by the stratification of slurry, the parameters of process are determined, the time of desulfurization slurry recovery treatment is shortened, and the calcium fluoride impurity content in gypsum in underflow is effectively reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of desulfurization slurry recovery technology for aluminum anode roasting flue gas, specifically a method for recovering and utilizing wet desulfurization slurry for aluminum anode roasting flue gas. Background Technology

[0002] Aluminum anode roasting flue gas refers to the waste gas generated during the production of prebaked anodes for aluminum electrolysis. Unlike general industrial waste gas, it contains pollutants such as sulfur dioxide, dust, asphalt fumes, and fluorides, in addition to sulfur dioxide and dust, which has a significant impact on the environment. Therefore, anode roasting flue gas must be treated before being discharged. Currently, the mainstream treatment methods can be broadly divided into two types: dry desulfurization and wet desulfurization. Dry desulfurization has lower desulfurization efficiency and is gradually being phased out. Wet desulfurization has higher desulfurization efficiency, but it produces difficult-to-treat wastewater and sludge, which may cause secondary pollution.

[0003] Limestone-gypsum desulfurization is a mature wet desulfurization method. Its principle involves using a slurry made from limestone or quicklime to absorb sulfur dioxide from flue gas, generating calcium sulfite, which is then further oxidized into economically valuable gypsum. However, for flue gas from aluminum anode roasting, the traditional limestone-gypsum desulfurization method has certain limitations, specifically as follows: The desulfurization wastewater from aluminum anode roasting flue gas contains complex impurities, including heavy metals, halogens, and carbonaceous impurities. Among these, carbon ash, chloride ions, and fluoride ions may adsorb onto the surface of CaSO3·0.5H2O, forming physical or chemical barriers that hinder contact with oxygen and reduce the oxidation reaction rate. When oxidation is incomplete, CaSO3·0.5H2O cannot be completely converted to CaSO4·2H2O, resulting in excessively high calcium sulfite content in the slurry, forming fine needle-like or fibrous crystals instead of regular plate-like or columnar crystals. Heavy metal impurities, such as Al... 3+ Fe 3+ These substances can enter the gypsum crystal lattice or adhere to the crystal surface, altering the crystal growth rate and causing abnormal crystal growth direction, resulting in irregular shapes or aggregates. These tiny, irregular crystals have low packing density and numerous pores, making it difficult for moisture to escape, thus leading to an unstable gypsum structure.

[0004] Furthermore, these impurities may become trapped between gypsum crystals, blocking crystallization channels or altering the supersaturation of the slurry, leading to the rapid formation of numerous tiny crystal nuclei and resulting in gypsum products with small particles and unstable structures. In short, these impurities severely interfere with gypsum crystallization, causing a significant reduction in the yield and purity of gypsum products, and consequently, a decrease in economic benefits.

[0005] Therefore, there is an urgent need for a wet treatment method for the flue gas from aluminum anode baking, which can effectively recover high-quality gypsum and improve economic efficiency while ensuring rapid treatment. Summary of the Invention

[0006] The purpose of this invention is to overcome the shortcomings of the prior art and provide a method for recycling wet desulfurization slurry from aluminum anode roasting flue gas to at least achieve rapid and efficient recovery of high-quality gypsum.

[0007] The objective of this invention is achieved through the following technical solution: A method for recycling wet desulfurization slurry from aluminum anode roasting flue gas includes the following steps: S1: Take samples of the desulfurization slurry, adjust the pH value to 5.0~7.0, add aluminum salt, and determine the volume ratio of each layer in the slurry; S2: Adjust the pH of the desulfurization slurry to 5.0~7.0, add aluminum salt, and perform cyclone dewatering. Determine the overflow discharge amount according to the volume ratio of each layer determined in step S1 to obtain the overflow and underflow. S3: The underflow is dehydrated to obtain the finished gypsum product; S4: Collect and purify the overflow, then return it to the desulfurization tower.

[0008] In some embodiments, the evaluation method is as follows: In step S1, after the slurry is allowed to settle, it is divided into three layers, which are, from top to bottom, a clear liquid layer, an impurity layer and a gypsum crystal layer. The quality of the slurry is determined based on the volume of each layer in the slurry, and the corresponding treatment method is selected. When the volume of the impurity layer is two times or more than the volume of the gypsum crystal layer, the slurry quality is extremely poor. When the volume of the impurity layer is less than twice, half or more than twice the volume of the gypsum crystal layer, the slurry quality is poor. When the volume of the impurity layer is less than 1 / 2 of the volume of the gypsum crystal layer, the slurry quality is better.

[0009] In some examples, when the container for the slurry is a uniform container, the thickness of each layer can be used to determine the thickness.

[0010] In some examples, in step S2, when the slurry quality is extremely poor or poor, several centrifugal separations are performed, with a portion of the overflow being discharged each time, until the slurry quality is good when the sample is taken for testing, at which point the centrifugal separation is stopped, the underflow is obtained, and the overflow is combined; when the slurry quality is good, no additional processing is performed, and the overflow and underflow are obtained through a single centrifugal separation.

[0011] For example, when the slurry quality is poor, the overflow discharge volume during each centrifugation is 1.5~2m. 3 When the slurry quality is extremely poor, the overflow discharge volume during each centrifugation is 3~4m³. 3 .

[0012] In some examples, in steps S1 and S2, the aluminum salt is polyaluminum sulfate (PAS).

[0013] For example, in step S2, when the slurry quality is extremely poor, the amount of aluminum salt added is 500~2000 mg / L; when the slurry quality is relatively poor, the amount of aluminum salt added is 100~499 mg / L; when the slurry quality is relatively good, the amount of aluminum salt added is 20~99 mg / L.

[0014] In some embodiments, in step S3, the dehydration method includes vacuum belt dehydration, and the dehydration time is 4-6 hours.

[0015] In some embodiments, the purification method in step S4 is as follows: S5: Adjust the pH of the overflow to 9.0~9.5, allow it to settle, and then filter it; S6: Add limestone to the filtrate obtained in step S5, adjust the pH value to 5.0~7.0, allow precipitation, and filter to obtain the filtrate which can be returned to the desulfurization tower.

[0016] It is worth noting that aluminum salts are generally not introduced in conventional wet desulfurization processes because fluoride ions in the flue gas form complexes with aluminum ions, hindering the dissolution of limestone and reducing the desulfurization rate. However, this invention adds aluminum salts to the desulfurization slurry after the desulfurization tower. On one hand, this converts solid calcium fluoride impurities into complexes, removing fluoride ions from the underflow and significantly improving the purity of the gypsum product. On the other hand, the aluminum salts and their hydrolysis products have a flocculating effect, agglomerating suspended fly ash, fine particles, and tar in the slurry, reducing liquid turbidity, and significantly increasing the sedimentation and stratification rate of the slurry. This allows the invention to quickly determine the impurity content through sedimentation sampling, thereby determining subsequent process parameters, avoiding external sampling and inspection, greatly reducing processing costs, improving recovery efficiency, and shortening the processing time from the conventional 3-4 hours to 1-2 hours (excluding vacuum belt dewatering).

[0017] The beneficial effects of this invention are: 1. This invention accelerates the settling rate of desulfurization slurry by adding aluminum salts to it. Therefore, the impurity content can be quickly determined by the slurry stratification, thereby determining the parameters of the recovery process. This greatly shortens the time for desulfurization slurry recovery and treatment, saves disposal costs, and improves economic efficiency.

[0018] 2. This invention effectively reduces the calcium fluoride impurity content in the gypsum underflow by adding aluminum salts to the desulfurization slurry, thereby improving the purity of the gypsum product. Attached Figure Description

[0019] Figure 1 This is a photograph of the sedimentation stratification of the sample during sampling evaluation in Example 1 of the present invention.

[0020] Figure 2 This is a photograph of the sedimentation stratification of the sample for sampling judgment during cyclone dehydration in Example 1 of the present invention.

[0021] Figure 3 This is a photograph of the sedimentation stratification of the sample during sampling evaluation in Example 2 of the present invention. DETAILED DESCRIPTION OF THE EMBODIMENTS

[0022] The technical solution of the present invention will be further described in detail below with reference to the accompanying drawings, but the protection scope of the present invention is not limited to the following description.

[0023] Example 1 This example is used to provide a method for recycling wet desulfurization slurry from anode roasting flue gas for aluminum production, and the specific method is as follows: The desulfurization gypsum used in this example comes from the calcium-based desulfurization system supporting the anode roaster of Yunnan Yuanxin Carbon Co., Ltd.

[0024] 1) The desulfurization slurry discharged from the desulfurization tower is introduced into a pH test tank, the pH value is adjusted to 5~7 with dilute sulfuric acid / sodium carbonate, then 250 ml of the slurry is measured from the outlet of the pH test tank of the desulfurization tower using a 250 ml glass beaker, 500 mg of PAS (200 mesh) is added and mixed uniformly, and the mixture is allowed to stand for sedimentation for 2 hours. The result is shown in Figure 1 As shown, by visually observing the stratification characteristics of the sediment and the proportion of each layer (since the beaker is a uniform container, the comparison of the thickness of each layer can directly replace the comparison of the volume of each layer), it can be seen that the slurry is divided into three layers. At this time, the thickness of the second impurity layer is significantly higher than the thickness of the gypsum crystal layer at the bottom (the thickness of the impurity layer is ≥ 2 times the thickness of the gypsum crystal layer), which means the slurry has extremely poor quality and extremely high impurity content.

[0025] 2) PAS is added into the pH test tank at a dosage of 1500 mg / L, after stirring, the mixture is allowed to stand for 30 min, then the slurry is added into a gypsum cyclone. An external discharge branch pipe is arranged at the overflow pipe outlet of the gypsum cyclone, which is used to discharge the overflow during gypsum dehydration, and the overflow is passed from the discharge branch pipe into a storage tank with a stirring device (the effective volume of the storage tank is 18 m 3 ) for temporary storage.

[0026] During each cyclone dehydration, open the external discharge branch pipe to discharge the overflow for 1 hour (the sand settling nozzle of the cyclone uses a 16 mm specification, and the overflow discharge is about 3~4 m 3 ). After 3 times of dehydration, the sedimentation state of the slurry is observed. At this time, the thickness of the second impurity layer is equivalent to the thickness of the bottom gypsum crystal layer, as shown in Figure 2As shown (impurity layer thickness = gypsum crystal layer thickness), the slurry quality has improved, and the impurity content has decreased. Continue hydrocyclone dewatering once more. During gypsum dewatering, the hydrocyclone overflow is discharged for 30 minutes (using an 18mm hydrocyclone underflow nozzle, with approximately 1.5~2m of overflow discharged). 3 ).

[0027] The underflow was sent to a vacuum belt for dehydration for 4 hours to obtain a gypsum product with a moisture content of less than 15%.

[0028] 3) Flow the overflow from the storage tank into the wastewater sedimentation tank, adjust the pH value to 9.0~9.5, let it stand for 3 hours to precipitate heavy metal ions and heavy impurities, then discharge the supernatant to another wastewater sedimentation tank, add limestone to precipitate fluoride ions, then adjust the pH value to 5~7, let it stand for 30 minutes, and return the supernatant as recycled water to the desulfurization tower for limestone slurry recycling.

[0029] Example 2 This embodiment provides a method for recycling wet desulfurization slurry from aluminum anode roasting flue gas. The method is the same as in Embodiment 1, except that the desulfurization gypsum used is different, coming from different batches and different roasting furnaces, as detailed below: 1) The desulfurization slurry discharged from the desulfurization tower is introduced into a pH testing tank. The pH value is adjusted to 5-7 using dilute sulfuric acid / sodium carbonate. Then, 250ml of the slurry is measured from the outlet of the pH testing tank using a 250ml glass beaker, and 500mg of PAS (200 mesh) is added. The mixture is stirred evenly and allowed to settle for 2 hours. The results are as follows. Figure 3 As shown, by visually observing the stratification characteristics of the sediment and the proportion of each layer, it can be seen that the slurry is divided into three layers. At this time, the thickness of the second layer of impurities is significantly higher than the thickness of the bottom layer of gypsum crystals (the thickness of the impurity layer is less than 1 / 2 of the thickness of the gypsum crystal layer), which means that the slurry quality is good and the impurity content is low.

[0030] 2) Add PAS to the pH testing tank at a concentration of 1500 mg / L, stir, and let stand for 30 minutes. Then, add the slurry to the gypsum hydrocyclone. An external branch pipe is installed at the overflow outlet of the gypsum hydrocyclone to discharge the overflow during gypsum dewatering. The overflow flows from this branch pipe into a storage tank equipped with a stirring device (effective tank volume 18 m³). 3 (To be temporarily stored within)

[0031] After one cyclone dehydration, the underflow is sent to a vacuum belt for dehydration for 4 hours to obtain purified gypsum product.

[0032] 3) Flow the overflow from the storage tank into the wastewater sedimentation tank, adjust the pH value to 9.0~9.5, let it stand for 3 hours to precipitate heavy metal ions and heavy impurities, then discharge the supernatant to another wastewater sedimentation tank, add limestone to precipitate fluoride ions, then adjust the pH value to 5~7, let it stand for 30 minutes, and return the supernatant as recycled water to the desulfurization tower for recycling.

[0033] Comparative Example This experimental example provides a method for recycling wet desulfurization slurry from aluminum anode roasting flue gas. The method is a traditional method, and the desulfurization gypsum used is the same as in Example 1, as detailed below: The desulfurization slurry discharged from the desulfurization tower is introduced into a pH testing tank, where the wastewater is adjusted to a pH of 7.5-9.0 before being introduced into a flocculation tank (5m). 3 Add 2500g of PAC to the solution and stir rapidly for 2 minutes. Then add 25g of PAM and stir slowly for 15 minutes to induce flocculation. Allow the solution to settle, then filter the settled inorganic sludge using a screw press sludge dewatering machine to obtain crude gypsum. The clarified water is then returned to the desulfurization unit. The crude gypsum is then subjected to vacuum belt dewatering to obtain the final gypsum product.

[0034] Experimental Example This experiment was used to test the quality of the gypsum products obtained in Examples 1-2 and the comparative examples. The testing methods are shown in Table 1, and the test results are shown in Table 2 (some elements are expressed in their oxide form): Table 1

[0035] Table 2

[0036] As can be seen from the comparison between Example 1 and Comparative Example 1, for the same desulfurization slurry, the purified gypsum product obtained by the method of the present invention has a significantly higher Ca content. This indicates that the method of the present invention not only shortens the processing time by more than half compared with the traditional method, but also obtains a gypsum product with higher purity and lower fluoride content. Furthermore, the method uses only a small amount of additional reagents, resulting in lower processing costs for the desulfurization slurry.

[0037] The above description is merely a preferred embodiment of the present invention. It should be understood that the present invention is not limited to the forms disclosed herein and should not be construed as excluding other embodiments. It can be used in various other combinations, modifications, and environments, and can be altered within the scope of the concept described herein through the above teachings or related technologies or knowledge. Modifications and variations made by those skilled in the art that do not depart from the spirit and scope of the present invention should be within the protection scope of the appended claims.

Claims

1. A method for recycling wet desulfurization slurry from aluminum anode roasting flue gas, characterized in that, Includes the following steps: S1: Take samples of the desulfurization slurry, adjust the pH value to 5.0~7.0, add aluminum salt, and determine the volume ratio of each layer in the slurry; S2: Adjust the pH of the desulfurization slurry to 5.0~7.0, add aluminum salt, and perform cyclone dewatering. Determine the overflow discharge amount according to the volume ratio of each layer determined in step S1 to obtain the overflow and underflow. S3: The underflow is dehydrated to obtain the finished gypsum product; S4: Collect and purify the overflow, then return it to the desulfurization tower.

2. The recycling method according to claim 1, characterized in that, In step S1: after the slurry is allowed to settle, it separates into three layers, which are, from top to bottom, a clear liquid layer, an impurity layer, and a gypsum crystal layer. The quality of the slurry is determined based on the volume of each layer in the slurry, and the corresponding treatment method is selected. When the volume of the impurity layer is two times or more than the volume of the gypsum crystal layer, the slurry quality is extremely poor. When the volume of the impurity layer is less than twice, half or more than twice the volume of the gypsum crystal layer, the slurry quality is poor. When the volume of the impurity layer is less than 1 / 2 of the volume of the gypsum crystal layer, the slurry quality is better.

3. The recycling method according to claim 2, characterized in that: When the slurry quality is extremely poor or poor, several centrifugal separations are performed, with a portion of the overflow discharged each time, until the slurry quality is good when the sample is taken for testing. At this point, the centrifugal separation is stopped, and the underflow is obtained and the overflow is combined. When the slurry quality is good, no additional treatment is performed, and the overflow and underflow are obtained through a single centrifugal separation.

4. The recycling method according to claim 3, characterized in that: When the pulp quality is poor, the overflow discharge is 1.5-2 m3 per centrifugation 3 When the pulp quality is very poor, the overflow discharge is 3-4 m3 per centrifugation 3 .

5. The recycling method according to claim 2, characterized in that: In steps S1 and S2, the aluminum salt is aluminum polysulfate.

6. The recycling method according to claim 5, characterized in that: In step S2, when the slurry quality is extremely poor, the amount of aluminum salt added is 500~2000 mg / L; when the slurry quality is relatively poor, the amount of aluminum salt added is 100~499 mg / L; when the slurry quality is relatively good, the amount of aluminum salt added is 20~99 mg / L.

7. The recycling method according to claim 1, characterized in that: In step S3, the dehydration method includes vacuum belt dehydration, and the dehydration time is 4~6 hours.

8. The recycling method according to claim 1, characterized in that: In step S4, the purification method is as follows: S5: Adjust the pH of the overflow to 9.0~9.5, allow it to settle, and then filter it; S6: Add limestone to the filtrate obtained in step S5, adjust the pH value to 5.0~7.0, allow precipitation, and filter to obtain the filtrate which can be returned to the desulfurization tower.